Role of Lipid Metabolism and Signaling in Mammalian Oocyte Maturation, Quality, and Acquisition of Competence - Khan, Ranjha; Jiang, Xiaohua; Hameed, Uzma; Shi, Qinghua (Frontiers in Cell and Developmental Biology, 2021)
It has been found that the quality of oocytes from obese women has been compromised and subsequent embryos displayed arrested development. The compromised quality may be either due to the poor or rich metabolic conditions such as imbalance or excession of lipids during oocyte development. Generally, lipids are mainly stored in the form of lipid droplets and are an important source of energy metabolism. Similarly, lipids are also essential signaling molecules involved in various biological cascades of oocyte maturation, growth and oocyte competence acquisition. To understand the role of lipids in controlling the oocyte development, we have comprehensively and concisely reviewed the literature and described the role of lipid metabolism in oocyte quality and maturation. Moreover, we have also presented a simplified model of fatty acid metabolism along with its implication on determining the oocyte quality and cryopreservation for fertilization.